Motivational Factors for the Implementation of ISO-9001 in Construction Firms of Pakistan - Akhund, Muhammad Akram; Memon, Aftab Hameed; Imad, Hafiz Usama; Siddiqui, Fida Hussain; Khoso, Ali Raza (Civil Engineering Journal, 2018)
Motivating public and private construction firms to implement various management systems in their firms is not a simple job. Especially in Pakistan, management system is a new practice, most of the construction firms are not aware about the benefits of management system and what will be achieved after the implementation of management system. The implementation of ISO 9001 Quality Management System (QMS) in the construction industry is a continuing development method, particularly in small construction firms. On the other hand, the awareness level and readiness level of construction industry firms in Pakistan is yet very low as associated to other countries of Asia and Europe where ISO 9001 initiated. The purpose current study is to determine most responsible factors which will motivate the public and private construction firms of Pakistan to adopt the QMS (ISO 9001). A questionnaire survey was conducted and a total of 337 out of 553 questionnaires were received from public and private construction firms of AZBAGIKHPUSI areas. The analysis results depict 3 significant factors, which will motivate construction firms of Pakistan to implement ISO 9001 are (1) to qualify for bidding (2) to improve quality management system of company (3) to reduce wastage. Hence, based on these results and findings, the construction companies require ISO 9001 certification system and registration with Pakistan Engineering Council (PEC) as a constitution passed for the construction firms then to qualify for the bidding.